2022
DOI: 10.1017/s0007114522001301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of collagen peptide supplementation on cardiovascular markers: a systematic review and meta-analysis of randomised, placebo-controlled trials

Abstract: Previous studies have advocated that collagen peptide supplementation (CPS) can positively affect cardiovascular health. However, the widespread impact of CPS on cardiovascular disease-related markers is not fully resolved. Consequently, the current systematic review and meta-analysis aimed to assess the efficacy of CPS on cardiovascular disease-related markers. A systematic search in the Scopus, PubMed, and ISI Web of Science databases were completed to identify relevant randomized, placebo-controlled trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…In line with the findings of two systematic reviews [39,52], significant favorable body composition changes have been observed following several weeks of consuming CP together with either resistance (RT) or concurrent (CT) training with a moderate certainty of evidence. Furthermore, the current meta-analysis demonstrated enhanced fat-free mass (FFM) along with muscle architectural adaptations, expressed as augmentations in one-, two-, and three-dimensional measurements.…”
Section: Discussionsupporting
confidence: 65%
“…In line with the findings of two systematic reviews [39,52], significant favorable body composition changes have been observed following several weeks of consuming CP together with either resistance (RT) or concurrent (CT) training with a moderate certainty of evidence. Furthermore, the current meta-analysis demonstrated enhanced fat-free mass (FFM) along with muscle architectural adaptations, expressed as augmentations in one-, two-, and three-dimensional measurements.…”
Section: Discussionsupporting
confidence: 65%